Impact of number of [18F]fluorodeoxyglucose-PET-positive lymph nodes on survival of patients receiving neoadjuvant chemotherapy and surgery for oesophageal cancer. Issue 1 (27th October 2015) - Miyata, H; Yamasaki, M; Makino, T; Tatsumi, M; Miyazaki, Y; Takahashi, T; Kurokawa, Y; Takiguchi, S; Mori, M; Doki, Y
Abstract: Background: [ 18 F]fluorodeoxyglucose (FDG)-PET has been used to evaluate the response of primary tumours to neoadjuvant therapy for oesophageal cancer. The clinical significance of the number of PET-positive nodes before and after therapy has not been investigated previously. Methods: [ 18 F] FDG-PET was performed before and 2–3 weeks after completion of neoadjuvant chemotherapy to identify the number of PET-positive nodes, and these numbers were assessed in relation to metabolic changes in the primary tumour. Results: Of 302 patients in total, 90 had no PET-positive nodes, 83 had one, 59 had two and 70 patients had three or more positive nodes before therapy. After treatment, the numbers were: none in 207 patients, one in 59, two in 20 and three or more in 16 patients. The number of PET-positive nodes after treatment was influenced by both the number of PET-positive nodes before therapy and the response to preoperative therapy, and correlated with the number of metastatic lymph nodes. Overall survival was longer in patients who had no PET-positive nodes after treatment than in those who had one or more. Multivariable analysis identified the numbers of PET-positive nodes before and after chemotherapy as independent prognostic factors, together with clinical response, tumour depth and lymph node involvement. Conclusion: The number of PET-positive nodes after treatment correlated with survival in patients with oesophageal cancer who underwent neoadjuvant chemotherapy. Abstract : Dismal prognosis if PET-positive nodes exist after treatment